The Effect of Elephant Foot Yam (Amorphophallus campanulatus) Flour and Soybean Oil Addition on the Physicochemical and Sensory Properties of Beef Sausage - Eny Sri Widiastuti; Djalal Rosyidi; Lilik Eka Radiati; Purwadi Purwadi (Faculty of Animal Science Universitas Brawijaya, 2020)
The texture of sausage was affected by its binding agent. Elephant foot yam (Amorphophallus campanulatus) flour was a potential natural binding agent and filler for sausage. The objective of this study was to evaluate the effect of elephant foot yam flour and soybean oil addition to the physicochemical properties and sensory attributes of beef sausage. A randomized block design with two factors and three replications were employed. Three addition levels (10%, 15% and 20% of meat weight) were used for both elephant foot yam flour and soybean oil. The results showed that the addition of elephant foot yam flour significantly (P≤0.01) affect the water-holding capacity (WHC) and sausage texture. The effect (P≤0.05) was also observed on the redness color (a* value). However, no effect was found on pH, L and b* values. On the other hand, the WHC and sausage texture were also significantly (P≤0.05) affected by soybean oil addition without altering pH and color. The highest addition level (20%) for both elephant foot yam flour and soybean oil showed a firm and compact beef sausage micro-structure with small pores. The highest fat and crude fiber content were also found in this group (20% addition level) and the sensory attributes (texture, aroma and taste) of the former group were comparable with the group with lowest addition level (10%). Therefore, elephant foot yam flour can be used as filler for producing both reduced-fat and typical beef sausage.